Self-delivering RNAi immunotherapeutic PH-762 silences PD-1 to generate local and abscopal antitumor efficacy - Cuiffo, Benjamin; Maxwell, Melissa; Yan, Dingxue; Guemiri, Ramdane; Boone, Andrew; Bellet, Deborah; Rivest, Brianna; Cardia, James; Robert, Caroline; Fricker, Simon P. (Frontiers in Immunology, 2024)
ObjectiveImmunotherapeutic inhibition of PD-1 by systemically administered monoclonal antibodies is widely used in cancer treatment, but it may cause severe immune-related adverse events (irSAEs). Neoadjuvant PD-1 inhibition before surgery has shown promise in reducing recurrence by stimulating durable antitumor immunity. Local intratumoral (IT) immunotherapy is a potential strategy to minimize irSAEs, but antibodies have limited tumor penetration, making them less suitable for this approach. Therapeutic self-delivering RNAi (INTASYL) is an emerging modality well-suited for neoadjuvant immunotherapy. This study presents preclinical proof-of-concept for PH-762, an INTASYL designed to silence PD-1, currently in clinical development for advanced cutaneous malignancies (ClinicalTrials.gov#NCT06014086).Methods and analysisPH-762 pharmacology was characterized in vitro, and in vivo antitumor efficacy was evaluated using a murine analogue (mPH-762) in syngeneic tumor models with varying PD-1 responsiveness. Bilateral Hepa1-6 models assessed abscopal effects of local treatment. Ex vivo analyses explored mechanisms of direct and abscopal efficacy.ResultsPH-762 was rapidly internalized by human T cells, silencing PD-1 mRNA and decreasing PD-1 surface protein, enhancing TCR-stimulated IFN-γ and CXCL10 secretion. In vivo, IT mPH-762 provided robust antitumor efficacy, local and lymphatic biodistribution, and was well tolerated. Ex vivo analyses revealed that IT mPH-762 depleted PD-1 protein, promoted leukocyte and T cell infiltration, and correlated with tumor control. IT mPH-762 also demonstrated efficacy against untreated distal tumors (abscopal effect) by priming systemic antitumor immunity.ConclusionThese data support PH-762 as a promising candidate for neoadjuvant immunotherapy in clinical studies.